Timing of Caffeine Therapy and Neonatal Outcomes in Preterm Infants: A Retrospective Study. (8th May 2016) - Hand, Ivan; Zaghloul, Nahla; Barash, Lily; Parris, Rudolph; Aden, Ulrika; Li, Hsiu-Ling
Abstract : Background . Caffeine is widely used to treat apnea of prematurity. Here, we evaluated the efficacy of early caffeine (1-2 DOL) in decreasing the incidence of adverse neonatal outcomes. Methods . A retrospective cohort was used to compare the neonatal morbidity of 150 preterm neonates with gestational age ≤29 weeks. Infants were divided into 3 groups based on the initiation timing of caffeine therapy; (1) early caffeine (1-2 DOL), (2) late caffeine (3–7 DOL), and (3) very late caffeine (≥8 DOL). Results . The neonatal outcomes of early caffeine were comparable with those of the late caffeine group. Moreover, when comparing the neonatal morbidity of the very late caffeine group with that of the early caffeine group, multivariable logistic regression analyses were performed. We found that the timing of caffeine did not influence the risk of BPD (OR, 0.393; CI, 0.126–1.223; p = 0.107 ), but birthweight did (OR, 0.996; CI, 0.993–0.999; p = 0.018 ) in these infants. Conclusion . Neonatal outcomes of preterm infants were comparable whether caffeine was administered early or late in the first 7 DOL. The risk of BPD in infants receiving caffeine after 8 DOL was irrespective of delayed treatment with caffeine. Our results clearly demonstrate the need for further studies before caffeine prophylaxis can be universally recommended.